2023
DOI: 10.3390/bios13070682
|View full text |Cite
|
Sign up to set email alerts
|

A Prototype Assay Multiplexing SARS-CoV-2 3CL-Protease and Angiotensin-Converting Enzyme 2 for Saliva-Based Diagnostics in COVID-19

Vallabh Suresh,
Daniel A. Sheik,
Tyler C. Detomasi
et al.

Abstract: With the current state of COVID-19 changing from a pandemic to being more endemic, the priorities of diagnostics will likely vary from rapid detection to stratification for the treatment of the most vulnerable patients. Such patient stratification can be facilitated using multiple markers, including SARS-CoV-2-specific viral enzymes, like the 3CL protease, and viral-life-cycle-associated host proteins, such as ACE2. To enable future explorations, we have developed a fluorescent and Raman spectroscopic SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…The authors of this review have translated assays using Raman-active dyes that have shown detection limits below those of traditional fluorescence measurements ( 71 ). Furthermore, Suresh et al have published the first example of translating a SERS assay for protease activity of gastricsin to a clinically ready platform with a small cohort of human pancreatic cyst fluid samples ( 72 ).…”
Section: Advanced Research Geared Toward Clinical Translationmentioning
confidence: 99%
“…The authors of this review have translated assays using Raman-active dyes that have shown detection limits below those of traditional fluorescence measurements ( 71 ). Furthermore, Suresh et al have published the first example of translating a SERS assay for protease activity of gastricsin to a clinically ready platform with a small cohort of human pancreatic cyst fluid samples ( 72 ).…”
Section: Advanced Research Geared Toward Clinical Translationmentioning
confidence: 99%